Lower Permian basaltic agglomerate from the Tsengel River valley, Mongolian Altai - Hrdličková, Kristýna; Battushig, Altanbaatar; Hanžl, Pavel; Zavřelová, Alice; Míková, Jitka (Mongolian Geoscientist, 2020)
A new occurrence of Permian volcanic and volcaniclastic rocks in the Mongolian Altai south of the Main Mongolian Lineament was described between soums of Tugrug and Tseel in Gobi-Altai aimag. Studied vitrophyric pyroxene basalt lies in a layer of agglomerate and amygdaloidal lavas, which is a part of NE–SW trending subvertical sequence of varicolored siltstones and volcaniclastic rocks in the Tsengel River valley. This high-Mg basalt is enriched in large ion lithophile elements, Pb and Sr and depleted in Nb and Ta. LA-ICP-MS dating on 44 spots reveals several concordia clusters. The whole rock geochemistry of sample fits volcanic arc characteristic in the geotectonic discrimination diagrams. Dominant zircon data yield Upper Carboniferous and Permian magmatic ages 304.4 ± 2.3 and 288.6 ± 1.9 Ma. Two smaller clusters of Upper Devonian (376 ± 4.7 Ma) to Lower Carboniferous ages (351.9 ± 3.5 Ma) indicate probably contamination of ascending magmatic material. Youngest Triassic age found in three morphologically differing grains reflects probably lead loss. Described high-Mg basalt lava represents sub-aerial volcanism in volcanic arc environment developed over the N dipping subduction zone in the southwestern Mongolia in the time span from Uppermost Carboniferous to Permian during terminal stage of its activity.